SPR biosensor for quantification of fetuin-A as a promising multibiomarker - Riedelová, Z; Májek, P; Pečánková, K; Kučerová, J; Surman, F; Pereira, A De Los Santos; Riedel, T (Physiological research, 2018)
Early diagnosis of ongoing malignant disease is crucial to improve survival rate and life quality of the patients and requires sensitive detection of specific biomarkers e.g. prostate-specific antigen (PSA), carcinoembryonic antigen (CEA), alpha-fetoprotein (AFP), etc. In spite of current technological advances, malignant diseases are still identified in rather late stages, which have detrimental effect on the prognosis and treatment of the disease. Here, we present a biosensor able to detect fetuin-A, a potential multibiomarker. The biosensing platform is based on polymer brush combining antifouling monomer units of N-(2-hydroxypropyl)methacrylamide (HPMA) and carboxybetaine methacrylamide (CBMAA), statistically copolymerized by surfaceinitiated atom transfer radical polymerization. The copolymer poly(HPMA-co-CBMAA) exhibits excellent non-fouling properties in the most relevant biological media (i.e. blood plasma) as well as antithrombogenic surface properties by preventing the adhesion of blood components (i.e. leukocytes; platelets; and erythrocytes). Moreover, the polymer brush can be easily functionalized with biorecognition elements maintaining high resistance to blood fouling and the binding capacity can be regulated by tuning the ratio between CBMAA and HPMA units. The superior antifouling properties of the copolymer even after biofunctionalization were exploited to fabricate a new plasmonic biosensor for the analysis of fetuin-A in real clinical blood plasma samples. The assay used in this work can be explored as labelfree affinity biosensor for diagnostics of different biomarkers in real clinical plasma samples and to shift the early biomarker detection toward novel biosensor technologies allowing point of care analysis.
Keywords: biosenzitivní techniky; Surface Plasmon Resonance; fetuin A; Humans; alpha-2-HS-Glycoprotein; lidé; povrchová plasmonová rezonance; biologické markery; Biomarkers; Biosensing Techniques